1998
DOI: 10.1111/j.1399-0039.1998.tb03074.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of insulin‐dependent diabetes mellitus (IDDM)‐related HLA alleles correlates with the difference in IDDM incidence in four populations of the Eastern Baltic region

Abstract: The high incidence of insulin-dependent diabetes mellitus (IDDM) in Finland contrasts strikingly with the low rates in the neighbouring populations of countries in the Eastern Baltic region: Estonia, Latvia and Russia. To evaluate the possible contribution of genetic factors to these differences, the frequencies of HLA-DQB1 alleles and relevant DQB1-DQA1 or DQB1-DRB1 haplotypes associated with IDDM risk or protection were analysed among IDDM patients and control subjects from these four populations. An increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 12 publications
(7 reference statements)
6
23
1
Order By: Relevance
“…In this respect, it is interesting to note that when comparing the frequencies of the HLA DR3-DQ2/DR4-DQ8 genotype in patients with T1D in Europe, we observed that this high risk genotype was more prevalent in patients from countries with a low disease incidence suggesting that these populations are at an earlier stage of the natural evolution of diabetes history [15,16]. The declining protective efficiency of DQB1*0603 is reflected in fact in the behaviour of the DQB1*0302/DQB1*0603 genotype which was increased among patients diagnosed during the later time period and we observed this particular genotype to be associated with T1D in Finland, whereas in several other populations with lower diabetes incidence no such disease association has been detected [17].…”
Section: Discussionmentioning
confidence: 97%
“…In this respect, it is interesting to note that when comparing the frequencies of the HLA DR3-DQ2/DR4-DQ8 genotype in patients with T1D in Europe, we observed that this high risk genotype was more prevalent in patients from countries with a low disease incidence suggesting that these populations are at an earlier stage of the natural evolution of diabetes history [15,16]. The declining protective efficiency of DQB1*0603 is reflected in fact in the behaviour of the DQB1*0302/DQB1*0603 genotype which was increased among patients diagnosed during the later time period and we observed this particular genotype to be associated with T1D in Finland, whereas in several other populations with lower diabetes incidence no such disease association has been detected [17].…”
Section: Discussionmentioning
confidence: 97%
“…A significant contribution to type 1 diabetes genetic susceptibility appears to be encoded by the HLA DQB1 locus and in particular by DQB1*0302 and DQB1*0201, found on the DR4 and DR3 haplotypes, respectively [7,8]. Although the DQB1 locus still represents the single most important indicator of susceptibility, DQA1*0501 and DQA1*0201 are both associated with type 1 diabetes [9].…”
Section: Introductionmentioning
confidence: 98%
“…No reasonable further analyses can be based on this incomplete information. As a control we used background population frequencies of the class II haplotypes established in a previous study of the same populations (15).…”
Section: Methodsmentioning
confidence: 99%